2016
DOI: 10.3390/ijms17040486
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Specific Viruses on Clinical Outcome in Children Presenting with Acute Heart Failure

Abstract: The presence and type of viral genomes have been suggested as the main etiology for inflammatory dilated cardiomyopathy. Information on the clinical implication of this finding in a large population of children is lacking. We evaluated the prevalence, type, and clinical impact of specific viral genomes in endomyocardial biopsies (EMB) collected between 2001 and 2013 among 63 children admitted to our hospital for acute heart failure (median age 2.8 years). Viral genome was searched by polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…Prognostic studies of the presence of B19V in EMB in children are contradictory and scarce ( Table ). A recent study showed a better outcome for children with a virus‐positive EMB (mainly B19V) . In accord with these results, viral presence had no influence on outcome in another study .…”
Section: Parvovirus B19‐related Heart Disease In Childrensupporting
confidence: 52%
“…Prognostic studies of the presence of B19V in EMB in children are contradictory and scarce ( Table ). A recent study showed a better outcome for children with a virus‐positive EMB (mainly B19V) . In accord with these results, viral presence had no influence on outcome in another study .…”
Section: Parvovirus B19‐related Heart Disease In Childrensupporting
confidence: 52%
“…7274 Parvovirus B19, influenza, Epstein-Barr, HIV, coxsackie virus, herpes, and adenovirus have all been identified. 7377 Murine models of myocarditis (coxsackie or adenoviral) demonstrate evidence of disruption of several important pathways in the innate and activated immune systems. 78, 79 The enteroviral protease 2A has been demonstrated to cleave the cytoskeletal protein- dystrophin which results in severe DCM.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%
“…Potential targets for investigation include genetic variants, circulating or imaging markers of inflammation or stress, neurohormonal abnormalities, microRNA, viral genome on endomyocardial biopsy, and markers of extracardiac impairment. 51, 73, 74, 94, 101, 102, 108, 109 Identifying biomarkers that are important for pediatric patients is the focus of a large ongoing study by the PCMR and is an area of research need.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%
“…19 Parvovirus B19 and Epstein-Barr virus are most frequently isolated by cardiac biopsy in children. 86,87 About one fourth of children with DCM have underlying neuromuscular disorders, specifically Duchenne and Becker muscular dystrophies. 88 Overall, DCM seems to have a worse prognosis in children than in adults.…”
Section: Pediatric Cardiomyopathiesmentioning
confidence: 99%
“…86,87 Our understanding of this cardiomyopathy is still relatively primitive. It is not clear how often it represents a congenital disorder based on an embryological defect in children.…”
Section: Pediatric Cardiomyopathiesmentioning
confidence: 99%